2012
DOI: 10.2174/157488612802715744
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin-induced Hypoglycemia in a Non-diabetic Patient

Abstract: Hypoglycemia is a rare life threatening adverse drug reaction associated with various fluoroquinolones like ciprofloxacin, gatifloxacin and levofloxacin. Moxifloxacin was considered safe in this regard. Only one case has been reported for moxifloxacin-induced hypoglycemia in a renal failure patient. Here, we are reporting the second case of hypoglycemia due to moxifloxacin without any major co-morbid condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…We observed a classical surge in the serum insulin levels with a subsequent decrease in the blood glucose levels. Though there are reports of dysglycemia regarding the use of fluoroquinolones in treating different ailments with quinolones, previous case studies reported that quinolones induce dysglycemia [ 17 , 18 , 19 , 20 ]. However, there are also reports of hyperglycemia with Moxifloxacin , Gatifloxacin , and levofloxacin .…”
Section: Discussionmentioning
confidence: 99%
“…We observed a classical surge in the serum insulin levels with a subsequent decrease in the blood glucose levels. Though there are reports of dysglycemia regarding the use of fluoroquinolones in treating different ailments with quinolones, previous case studies reported that quinolones induce dysglycemia [ 17 , 18 , 19 , 20 ]. However, there are also reports of hyperglycemia with Moxifloxacin , Gatifloxacin , and levofloxacin .…”
Section: Discussionmentioning
confidence: 99%
“…Although the metabolism of paracetamol can be decreased when combined with MOXI, if you need a pain killer it is however fine to take paracetamol with MOXI. For example, patients receiving 200 mg MOXI orally each half day could also take 500 mg paracetamol in case of dry cough and high fever rate [10]. So, the simultaneous detection of MOXI and paracetamol is of interest.…”
Section: Resultsmentioning
confidence: 99%
“…[234] In the literature there are only two case reports of moxifloxacin induced hypoglycemia. [56] These were published in last 1 year and the patients were non-diabetic.…”
Section: Discussionmentioning
confidence: 99%